ORIENTASI LISAN DALAM SAJAK-SAJAK UPITA AGUSTINE - Sastri Sunarti (Faculty of Humanities, Jember University, 2013)
Orality or oral oriented in Upita Agustine’s poetry could be recognized by formula and formulaic compotition which defined by Lord and Sweeney. This formula found in 62 numbers of Upita’s poetry. The formula in that poetry are formula’s begin of the lines, formula’s the half of lines, and formula’s the end of lines. Beside using the formula, we could find some compotition formulaic and stylized form in Upita’s poetry. Oral oriented in Upita’s poetry commonly used by unconsiousness. Keywords: oral oriented, formula, formulaic compotition, stylized form